Assessment of biomarkers of exposure and potential harm, and physiological and subjective health measures in exclusive users of nicotine pouches and current, former and never smokers. (2nd January 2023) - Azzopardi, David; Haswell, Linsey E.; Frosina, Justin; McEwan, Michael; Gale, Nathan; Thissen, Jesse; Meichanetzidis, Filimon; Hardie, George
Abstract: Background: Oral nicotine pouches (NPs) are smokeless, tobacco-free products that have a potential role in tobacco harm reduction strategies. Methods: In a cross-sectional study in Sweden/Denmark, several recognised biomarkers of potential harm (BoPHs) linked to smoking-related diseases/their initiating biological processes, and biomarkers of exposure (BoEs) to tobacco/tobacco smoke toxicants were compared among exclusive adult users of Velo NPs and current/former/never smokers. Over 24 h, participants used their usual product (Velo NP or cigarette) as normal, and BoEs/BoPHs were assessed via blood/24-h urine/exhaled breath/physiological assessments. Results: Among the primary endpoints, total NNAL (16.9 ± 29.47 vs 187.4 ± 228.93 pg/24 h), white blood cell count (5.59 ± 1.223 vs 6.90 ± 1.758 × 10 9 /L), and COHb (4.36 ± 0.525 vs 8.03 ± 2.173% saturation) were significantly lower among Velo users than among smokers (91%, 19% and 46% lower, respectively, all P < 0.0001), while fractional exhaled NO, previously shown to be lower in smokers, was significantly higher (23.18 ± 17.909 vs 11.20 ± 6.980 ppb) among Velo users (107% higher, P < 0.0001). Furthermore, sICAM-1 tended to be lower (185.9 ± 42.88 vs 204.5 ± 64.85 ng/mL) among Velo users than smokers (9% lower). Several secondary endpoints, including six BoEs (3-HPMA (246.7 ± 91.07 vs 1165.7 ± 718.35 μg/24 h), 3-OH-B[ a ]P (82.4 ± 217.58 vs 258.3 ± 190.20 pg/24 h), HMPMA (135.1 ± 77.85 vs 368.8 ± 183.15 μg/24 h), MHBMA (0.22 ± 0.166 vs 3.39 ± 2.943 μg/24 h), S-PMA (0.10 ± 0.059 vs 3.53 ± 2.736 µg/24 h) and total NNN (7.5 ± 24.84 vs 9.7 ± 5.93 ng/24 h)), were significantly lower among Velo users (78.8%, 68.1%, 63.4%, 93.5%, 97.2% and 22.7% lower, respectively, P < 0.0001–0.0011), while total nicotine equivalents was significantly higher among Velo users (22.6 ± 12.69 vs 12.1 ± 7.92 mg/24 h, P < 0.0001), although Velo user levels are comparable to those previously reported among oral tobacco users, and Velo user and smoker mean levels were similar in Denmark. Conclusion: As compared with smokers, exclusive users of Velo NPs have significantly less exposure to tobacco toxicants and more favourable BoPHs associated with initiating biological processes of smoking-related diseases. International Standard Registered Clinical Trial number: ISRCTN16988167